Effect of hand paddles and parachute on backstroke coordination and stroke parameters. Issue 9 (3rd May 2017) - Telles, Thiago; Barroso, Renato; Figueiredo, Pedro; Salgueiro, Diego Fortes de Souza; Vilas-Boas, João Paulo; Junior, Orival Andries
ABSTRACT: Hand paddles and parachutes have been used in order to overload swimmers, and consequently increase the propulsive force generation in swimming. However, their use may affect not only kinematical parameters (average speed, stroke length and stroke rate), but also time gaps between propulsive phases, assessed through the index of coordination (IdC). The objective of this study was to assess the effects of hand paddles and parachute use, isolated or combined, on kinematical parameters and coordination. Eleven swimmers (backstroke 50-m time: 29.16 ± 1.43 s) performed four 15-m trials in a randomised order at maximal intensity: (1) without implements (FREE), (2) with hand paddles (HPD), (3) with parachute (PCH) and (4) with hand paddles plus parachute (HPD+PCH). All trials were video-recorded (60 Hz) in order to assess average speed, stroke rate, stroke length, five stroke phases and index of coordination. When average swimming speed was compared to FREE, it was lower in PCH and HPD+PCH, and higher in HPD. Stroke rate decreased in all overloaded trials compared to FREE. The use of hand paddles and parachute increased and decreased stroke length, respectively. In addition, propulsive phase duration was increased when hand paddles were used, and time gaps shifted towards zero (no time gap), especially when hand paddles were combined with parachute. It is conceivable that the combined use of hand paddles and parachute, once allowing overloading both propulsive and resistive forces, provides a specific stimulus to improve muscle strength and propulsive continuity.